Determining the Extent of Use of Electronic Information Resources by the Distance Learners - Kato, Agrey (Qualitative and Quantitative Methods in Libraries; Vol 10 No 3 (2021): September issue 2021, 2021)
This paper presents an analysis survey of the Nelson Mandela African Institution of Science & Technology (NM-AIST), the University of Dar es Salaam (UDSM), and Mzumbe University (MU). The survey aimed to assess the degree to which the academic community uses electronic information resources (EIRs). Data were collected using questionnaires and both quantitative and qualitative methods were used in the methodology. The entire population in selected institutions was very large and 5258 library users were selected using the Kish formula for cross-sectional studies and the convenient sample size was chosen including 120, 4888, and 250 library users from NM-AIST, UDSM, and MU respectively under purposive sampling technique. The study found that 1217 (73%) of the respondents were aware of EIRs but had limited access because of social and technical challenges. The results conclude that users need practical information-retrieval skills and library managers should ensure adequate infrastructure to facilitate the productive use of EIRs.